(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The present research has the purpose of responding to the integration of a space through the architectural design of a geoscience museum, dedicated to the geology of our country since it is at the service of the research community where the design requirements are met . In Nicaragua, advances in geological studies have not had an adequate impulse where the teaching of basic principles of said research branch to the public is reduced, although there is no progress where the number of geological research centers at the level is taken into account. national, that is, the main geoscience study center is only in UNAN-Managua. The main focus of this museological design of geological pieces is to provide a better architectural development to the IGG-Cigeo laboratory facilities, and thus, provide alternatives by providing them with a better infrastructure that allows researchers, students and people in general to interact with the exhibited objects.